Pengaruh Variasi Elektroda untuk Penurunan Kadar TSS dan Kekeruhan Limbah Tekstil Batik Dalam Metode Elektrokoagulasi - Ramadhani, Audyna Ayu; Tuhu Agung Rachmanto (Jurnal Serambi Engineering, 2026)
The production of batik textiles causes serious environmental problems due to the direct discharge of wastewater into water bodies. The wastewater contains harmful substances that affect both living organisms and the environment. One effective treatment method is electrocoagulation, which combines electrochemical and flocculation–coagulation processes for wastewater treatment. This method reduces pollutant loads by varying electrode types. In this study, the electrodes used are Aluminum (Al), Iron (Fe), Copper (Cu), and Zinc (Zn) with contact times of 30, 60, 90, and 120 minutes. The electrodes are connected to a power supply and placed in an electrocoagulation reactor. The combination of electrode type and contact time significantly affects TSS (Total Suspended Solids) and turbidity. Longer contact time (30–120 minutes) leads to lower TSS and turbidity values due to the formation of Al(OH)₃ flocs, which adsorb suspended particles. The Al–Zn pair shows the best performance as it forms galvanic microcells that enhance metal ion dissolution. Statistical analysis reveals a strong correlation between TSS and turbidity, indicating effective treatment. Optimizing contact time improves electrocoagulation efficiency for batik wastewater treatment.